Chosen Problems of Spatial Planning in Poland - Brzeziński, Cezary (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
Spatial policy is one of the most important policies implemented by the municipal government policy alongside with economic and social development. A number of changes that have occurred since 1989 in the spatial planning led to increasing degradation of the space, excessive suburbanization, environmental and landscape devastation and infringement of economic basis of local governments. The article presents chosen problems that can be diagnosed in the Polish system of spatial planning.